Physiotherapy Examination Program for Especially Talented People (STP) - SOIna (Healthy Athletes Fun Fitness) - Mutia, Sri Alna; Kusma, Nila; Fithriany, Fithriany; Fadlina, Amelia; Agustina, Lisa (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
The Physiotherapy Program for Special Olympics Athlete Health Screening aims to improve the physical well-being and performance of athletes with special needs. Athletes participating in Special Olympics often face unique health challenges, including musculoskeletal issues, mobility limitations, and higher risk of injury. Therefore, this program is designed to provide a comprehensive evaluation of the athlete's physical condition and appropriate physiotherapy interventions. The main objectives of this program are to: Conducting comprehensive health screening for athletes before competition, identifying potential health problems or injuries that may affect athlete performance, providing personalized rehabilitation and training plans based on the results of the screening, increasing athlete knowledge about the importance of body care and injury prevention. The Program methodology involves several key steps: Initial Examination, Specific Testing, Physiotherapy Intervention and Athlete Education. Results: A Physiotherapy Examination Program, training and socialization of Physiotherapy for Special Talented People to improve fitness to train and improve athlete's body flexibility, functional body strength, aerobic capacity and balance, provide counseling to participants, families/parents of athletes, coaches, teachers in providing opportunities to learn about physical therapy and fitness, Parents, coaches and teachers listened and there was intense discussion and interaction. After the event was completed, a Whattsapp group was formed with teachers and physiotherapists to facilitate coordination and consultation regarding early detection and exercise therapy programs for children with special needs. Conclusion: The Physiotherapy health screening program for Special Olympics athletes is an important initiative in supporting the health and performance of athletes with special needs. With this comprehensive and evidence-based approach, it is expected to have a positive impact on the lives of athletes and improve their experience in competing. Keywords: Physiotherapy Examination, Athletes, Especially Talented People